Case Processing Time Standards in State Courts, 2002-2003 - (:unkn) unknown (My University, 2016)
The information in this report summarizes the latest available information about case processing time standards in use among state courts. Most of this information is current as of late 2002 or early 2003, but for states that have not responded to recent survey efforts, information may be from 1999 or even 1994. Obviously, the age of some of this information reduces the reliability of some statements with respect to aggregate data.